Cancer vaccines: methods and protocols - Lawman, Michael J. P.; Lawman, Patricia D. (Methods in molecular biology, 2014)
Single Step Antigen Loading and Maturation of Dendritic Cells Through mRNA Electroporation of a Tumor-Associated Antigen and a TriMix of Costimulatory Molecules -- Generation of Multiple Peptide Cocktail-Pulsed Dendritic Cells as a Cancer Vaccine -- Pulsing Dendritic Cells with Whole Tumor Cell Lysates -- Antigen Trapping by Dendritic Cells for Anti-Tumor Therapy -- Ex Vivo Loading of Autologous Dendritic Cells with Tumor Antigens -- Tumor Antigen/Cytokine-Pulsed Dendritic Cells in Therapy Against Lymphoma -- Dendritic Cells Primed with Protein-Protein Fusion Adjuvant -- Antigen-Specific mRNA Transfection of Autologous Dendritic Cells -- Electroporation of Dendritic Cells with Autologous Total RNA from Tumor Material -- Dendritic Cells Transfected with Adenoviral Vectors as Vaccines -- Genetic Modification of Dendritic Cells with RNAi -- Fast Monocyte-Derived Dendritic Cells-Based Immunotherapy -- Intratumoral Injection of BCG-CWS Pretreated Dendritic Cells Following Tumor Cryoablation -- Exploiting the CD1d-iNKT Cell Axis for Potentiation of DC-Based Cancer Vaccines -- Modification of T Lymphocytes to Express Tumor Antigens -- Genetic Modification of Mouse Effector and Helper T Lymphocytes Expressing a Chimeric Antigen Receptor -- Genetic Modification of Cytotoxic T Lymphocytes to Express Cytokine Receptors -- Monitoring the Frequency and Function of Regulatory T Cells and Summary of the Approaches Currently Used to Inhibit Regulatory T Cells in Cancer Patients -- Cytokine Activation of Natural Killer Cells -- Loading of Acute Myeloid Leukemia Cells with Poly(I:C) by Electroporation -- Autologous Tumor Cells Engineered to Express Bacterial Antigens -- Tumor Cell Transformation Using Antisense Oligonucleotide -- The Direct Display of Costimulatory Proteins on Tumor Cells as a Means of Vaccination for Cancer Immunotherapy -- Cloning Variable Region Genes of Clonal Lymphoma Immunoglobulin for Generating Patient-Specific Idiotype DNA Vaccine -- Heat Shock Proteins Purified from Autologous Tumors Using Antibody-Based Affinity Chromatography -- Invariant Chain-Peptide Fusion Vaccine Using HER-2/neu -- TLR-9 Agonist Immunostimulatory Sequence Adjuvants Linked to Cancer Antigens -- Production of Multiple CTL Epitopes from Multiple Tumor-Associated Antigens -- Preparation of Polypeptides Comprising Multiple TAA Peptides -- Idiotype Vaccine Production Using Hybridoma Technology -- Preparation of Cancer-Related Peptide Cocktails that Target Heterogeneously-Expressed Antigens -- Making an Avipoxvirus Encoding a Tumor-Associated Antigen and a Costimulatory Molecule -- Bacterial Vectors for the Delivery of Tumor Antigens -- Preparation of Peptide Microspheres Using Tumor Antigen-Derived Peptides -- Production of Antigen-Loaded Biodegradable Nanoparticles and Uptake by Dendritic Cells -- Development of Plasmid-Lipid Complexes for Direct Intratumoral Injection -- The Use of Dendritic Cells for Peptide-Based Vaccination in Cancer Immunotherapy -- Advances in Host and Vector Development for the Production of Plasmid DNA Vaccines -- Challenges Facing the Development of Cancer Vaccines -- Future of Cancer Vaccines.
Keywords: Aufsatzsammlung; Impfstoff; Krebs